Social Support Practices in Maintaining the Psychological Well-being of Students at Boarding-Based Islamic Senior High Schools - Assyifaul Aulia; Muh. Hanif (Journal Of Psychology, Counseling And Education, 2026)
This study aims to analyze the practice of social support in maintaining the psychological well-being of students at the boarding-based Madrasah Aliyah Negeri (MAN) 2 Banyumas. A qualitative approach was employed through in-depth observation, interviews with dormitory students and dormitory supervisors, as well as field observation checklists. The findings indicate that social support in the MAN 2 Banyumas dormitory is manifested across four primary dimensions: emotional support, instrumental support, informational support, and appraisal support. These dimensions are provided synergistically by dormitory supervisors, peers, and families. The tahfidz program, routine guidance sessions, a 41-day quarantine period, and a tiered warning system (SP1-SP3) serve as institutional instruments supporting the formation of a conducive social ecosystem for student well-being. These findings reinforce the relevance of sociological educational theory in understanding the role of boarding educational institutions as a structured social support system.